Testing and developing criteria and indicators for sustainable forest management in Cameroon: the Kribi test - Prabhu, Ravi; Maynard, W.; Eba'a Atyi, R.; Colfer, C.J.P.; Shepherd, G.; Venkateswarlu, P.; Tiayon, F. (Center for International Forestry Research, 1998)
This is the report of the Center for International Forestry Research (CIFOR) sixth test of criteria and indicators for sustainable forest management. The test took place in October and November 1996 in and around Kribi, Cameroon. Unlike previous criteria and indicators (C&I) tests, the Kribi test placed emphasis on testing methods for developing the C&I. Eighteen experts in forestry, ecology and social science from Cameroon and other countries were involved in testing C&I developed by ATO, a Dutch working group, and a set collated from several sources. As a result of the test a set of C&I deemed appropriate for the Kribi region was compiled and valuable feedback on the CIFOR method for iterative testing and development of C&I gained. This report will be useful for people interested in the process of developing C&I and for those interested in obtaining a model set of C&I for Central African conditions.